Konflik Politik Pada Pemilihan Umum Kepala Daerah (Studi Kasus di Kabupaten Puncak, Papua Tahun 2011-2012) - Yosin Kogoya; Achmad Nurmandi (Universitas Muhammadiyah Yogyakarta, 2015)
The implementation of direct elections is a from of regional autonomy in addition to the area where given the right toregulate its own territory, the people are also exempt determine their leaders. Unfortunately there is beyond theelections held in accordance with law and justice corridore, It triggers a conflict between elements of society andgovernment, as happened in the election of a Peak District, Papua years 2011-2012, the country peak conflict thatoccurs as a result dualism Gerindra party recommendations, which the DPP and DPD Gerindra party to give S.K SimonAlon-Josiah Tenbak as incumbent Gerindra, while DPC provide recommendations to Elvis Tabuni-party Herri Dosinaen,this in because there is an emotional bond between Thomas Tabuni (DPC chairman of the country party Gerindrapeak) as a child and Elvis Tabuni (district candidate) as a father.The type of the research conducted by the authors isto use a descriptive study, where the study site is Ilaga, peak district, while the authors explore how the information isto direct observation and interviews while also utilizing literature-literatur from the published literature and analysisused is purpose random sampling analysis using descriptive to analyze the data. The peak district of Puncak Jayadistrict Proliferation of 2007, and in 2011 made this a highlight of the country election that claimed the lives of 300people died and 900 people were injured, this conflict is a conflict since most victims in law election in Indonesia.Leveling system of one man one vote democracy make electoral conflicts in Papua can not be avoided due to theimmaturity of the people on the system, so that a recommendations is the author of the government to change thesystem becomes Nokens democratic systems, which is represented by the 1025 and 1 person as a democratic peopleof Papua.